2023
DOI: 10.1002/mnfr.202200264
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Visceral Fat is Associated with a Reduction in Inflammatory Status in Patients with Metabolic Syndrome

Abstract: Scope Excessive visceral adipose tissue (VAT) is associated with higher secretion of pro‐inflammatory molecules, contributing to systemic inflammation and obesity‐related metabolic disturbances. Methods and results This prospective analysis includes 117 overweight/obese adults (55–75 years) from the PREDIMED‐Plus study. Fourteen inflammatory markers and adipokines are measured using a Bio‐Plex assay with multiplex technology: insulin, glucagon, IL‐6, visfatin, ghrelin, GLP‐1, TNF‐α, MCP‐1, PAI‐1, resistin, C‐p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Nevertheless, the underlying mechanisms that explain the relationship between VAT and PD remain unclear. One possible explanation is that VAT might affect the immune system, causing changes in the inflammatory response (Castro‐Barquero et al, 2022) and the onset of PD (Machado et al, 2021). For example, VAT might affect the balance of pro‐inflammatory and anti‐inflammatory cytokines, resulting in increased inflammation and PD development (Czesnikiewicz‐Guzik et al, 2019; Kinane et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the underlying mechanisms that explain the relationship between VAT and PD remain unclear. One possible explanation is that VAT might affect the immune system, causing changes in the inflammatory response (Castro‐Barquero et al, 2022) and the onset of PD (Machado et al, 2021). For example, VAT might affect the balance of pro‐inflammatory and anti‐inflammatory cytokines, resulting in increased inflammation and PD development (Czesnikiewicz‐Guzik et al, 2019; Kinane et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Excess adiposity under these circumstances accelerates the aging process [12]. A few studies have reported the correlation between the changes in adipocytokine secretion with aging and obesity, under different dietary intervention, mostly in male mice [15][16][17][18][19][20]. Furthermore, fewer studies explore these changes in female mice [21].…”
Section: Introductionmentioning
confidence: 99%
“…Under these circumstances, excess adiposity accelerates the aging process [12]. A few studies have reported the correlation between the changes in adipocytokine secretion with aging and obesity under different dietary interventions, mostly in male mice [15][16][17][18][19][20]. Furthermore, fewer studies have explored these changes in female mice [21].…”
Section: Introductionmentioning
confidence: 99%